2015
DOI: 10.1270/jsbbs.65.177
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of <i>Arabidopsis thaliana</i> gibberellic acid 20 oxidase (AtGA20ox) gene enhance the vegetative growth and fiber quality in kenaf (<i>Hibiscus cannabinus</i> L.) plants

Abstract: Kenaf (Hibiscus cannabinus L.; Family: Malvaceae), is multipurpose crop, one of the potential alternatives of natural fiber for biocomposite materials. Longer fiber and higher cellulose contents are required for good quality biocomposite materials. However, average length of kenaf fiber (2.6 mm in bast and 1.28 mm in whole plant) is below the critical length (4 mm) for biocomposite production. Present study describes whether fiber length and cellulose content of kenaf plants could be enhanced by increasing GA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Fibre elongation rate was also maximized by spraying with GA 3 and fertilizing with NPK. Similarly, in transgenic kenaf and populus trees that over express gibberellic acid, the increased GA has a positive impact on fibre number, length, diameter, and wall thickness 27 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fibre elongation rate was also maximized by spraying with GA 3 and fertilizing with NPK. Similarly, in transgenic kenaf and populus trees that over express gibberellic acid, the increased GA has a positive impact on fibre number, length, diameter, and wall thickness 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, long okra fibres are stronger than short fibres because unlike long cells, short fibre cells require many weak connecting points in order to form fibre strands 29 . According to Withanage et al ., enhanced bioactive GA is extremely important for increasing the length of kenaf fibre and can be obtained by over expressing the Arabidopsis thaliana gibberellic acid 20 oxidase gene (AtGA20ox) in transgenic kenaf plants 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of transcriptomic profiling of hemp bast fibres at different developmental stages revealed that GA biosynthesis is significantly increased in the bark of bottom stem of hemp [2]. In addition, recent studies in ramie have also supported the role of GA in bast fiber development [4,49], and overexpression of the Arabidopsis gibberellic acid 20 oxidase (AtGA20ox) enhances vegetative growth and fiber quality in kenaf (Hibiscus cannabinus L.) plants [50,51]. GA was also proposed to function through promoting cambia cell proliferation to increase the cell amount of phloem tissue in Arabidopsis [52].…”
Section: Ethylene Might Be Involved In Vascular Maturation In Ramie'smentioning
confidence: 99%
“…A recent study of transcriptomic profiling of hemp bast fibres at different developmental stages revealed that GA biosynthesis is significantly increased in the bark of bottom stem of hemp [2]. In addition, recent studies in ramie have also supported the role of GA in bast fiber development [4,40], and overexpression of the Arabidopsis gibberellic acid 20 oxidase (AtGA20ox) enhances vegetative growth and fiber quality in kenaf (Hibiscus cannabinus L.) plants [41,42]. GA was also proposed to function through promoting cambia cell proliferation to increase the cell amount of phloem tissue in Arabidopsis [43].…”
Section: The Expression Of Ga Synthesis Enzymes and Ga Contents Altermentioning
confidence: 99%